Application of Natural Polymers in Wound Dressings - Maria Shahzadi, Taimoor Hassan, Sana Saeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Natural polymers because of their biodegradability, biocompatibility and closeness to the extracellular matrix are frequently used in regenerative medicine for burns and wound dressing. By triggering and stimulating the wound healing process, natural polymers aid in the restoration of damaged tissues and, as a result, skin regeneration1. Natural polymers have proven to be effective in a variety of biomedical applications, such as controlled administration of drugs, gene delivery, and regenerative medicine, among others.Plants, animals, and microbial are the major sources responsible for production of natural polymers. Based on their chemistry natural polymers are divided into polysaccharide, protein, polyester, and polyamide-based polymers2. Because of their 3 D cross-link-based networks of polymer, immersed with water or other biological fluids, hydrogels are considered worthwhile in the Biomedical and pharmaceutical industries for wound care, burn dressing, medication administration, tissue engineering and transplantation of organs3.